The case study of families with mental retarded children - O. V. Mikheykina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Dysfunction of family system can be seen as a deterrent of social adaptation of mentally retarded children. In this research there were investigated some specific psychological and social characteristics and needs to be dealt with and deserve consideration of rehabilitation service.